Strom, Kathryn J. and Adrian D. Martin. Becoming-Teacher: A Rhizomatic Look at First-Year Teaching. Sense Publishers, 2017, 138 pages. - Iwona Ionescu (Journal of the Assembly for Expanded Perspectives on Learning, 2024)
Becoming-Teacher: A Rhizomatic Look at First-Year Teaching - A Review